Challenging Masculinity: Analyzing the Aspects of Ecofeminism in Aceh’s Female Forest Rangers - Dewi, Karina Utami; Rohma, Masitoh Nur; Sabir, Husnul Ummahat (Parahyangan Center for International Studies, 2024)
This research discusses the issue of gender and environment in Southeast Asia and focuses on the casestudy of Female Forest Rangers or also known as Mpu Uteun in Aceh, Indonesia. It aims to answer the question: how do Female Forest Rangers in Aceh challenge masculinity and apply aspects of ecofeminism in protecting Aceh’s Forest? Using Warren’s approach of ecofeminism, the analysis of this research is divided into three parts. The first is masculinity and men’s role in Aceh’s environmental degradation, second is women and interconnection with nature, and third is ecofeminist philosophy in the case of Aceh’s female forest rangers. This study found that first, perpetrators of deforestation are mostly men as it is one of their ways to make a livelihood, enforcing a masculinity perspective that men should be dominating in providing for their family, including dominating the environment. Second, the female forest rangers have strong interconnections with nature since all the categories of interconnectedness between women and nature according to Warren can be found in this casestudy. Lastly, this case study can be claimed as an example of ecofeminist philosophy because the three aspects of Warren’s ecofeminist philosophy can be found in the research. These aspects are feminism; local and indigenous perspective; as well as nature, science, development, and technology. Keywords: Ecofeminism, masculinity, Aceh, Indonesia, female forest rangers